Pre-Service Teachers’ Perceptions on Their Professional Identity Development (PID) - Liwanag, Belinda A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research is focused on the perceptions of the pre-service teachers’ Professional Identity Development (PID). The respondents included 16 pre-service teachers from a private teacher education institution. It employed a descriptive narrative design with the qualitative method of collecting data using interview questionnaire and focus group discussion guideline as instruments. The findings showed all the shared experiences were perceived to be contributory to the development of the professional identity of the Pre-service Teachers (PTs) in the competencies stipulated in the Philippine Professional Standards for Teachers (PPST). Results of the interview done individually and as a group revealed how PTs perceived their professional identity development, which is essentially like the competencies of Stage 1 (Beginning Teacher). These include 1) Exhibiting mastery of concepts and pedagogy; 2) Effectiveness in communicating concepts; 3) Proficiency in information and communication technology (ICT) utilization; 4) Creating safe and conducive learning environment (classroom management); 5) Flexibility with the diverse learners; 6) Efficiency in lesson planning; 7) Consistency in reporting and monitoring learners’ progress; 8) Actively collaborating with colleagues and participating in the school community; and 9) Pursuing of continuous professional development. It proposes up-skilling and re-skilling of pre-service teachers which will all lead to the formation of a competent beginning teacher in the 21st century.